Control of carbon nanotube cantilever vibrator for nano-antenna applications. Issue 1 (1st January 2019) - Ghaffoori, Ali Jasim; Abdul-Adheem, Wameedh Riyadh
Abstract: The cantilever vibrator motion system of a carbon nanotube (CNT) is considered the next step in developing cold cathodes for VHF-band nano-antennas. In cases where a nano-antenna is used in noisy environments, this device interferes with other communication devices. In this paper, both the mechanical oscillation and the field electron emission of the CNT cantilever are modeled using the Wiener model. A control method is proposed based on the Wiener model for tracking the reception–emission current and reference emission current of the nano-antenna receiver by transforming the nonlinear control system into a simple linear system with satisfactory performance. In the nano-antenna receiver, the Wiener model offers the suppression of undesirable interference signals and noise to reduce the tracking error between the reception and reference signals by controlling the applied DC voltage as a function of the tracking error. A numerical simulation is implemented to realistically reflect the theoretical results, which show the suppression of the interference noise signal as compared with the conventional control scheme.